Reutilization Fast Hydrating Guar Fracturing Fluid - Qu, Zhanqing; Li, Xiaolong; Zhang, Jie; Su, Cheng; Lin, Shanshan (Asian Journal of Chemistry, 2013)
According to the low efficiency of fracturing fluid preparing in fracturing operation, the recent rising price of guar raw materials, too much drainage liquid after construction and the higher cost of treatment, fast hydrating guar fracturing fluid was developed and the feasibility of regeneration was studied. Based on a series of experiments, such as the rate of dissolution determination of the guar, the performance contrast between guar and conventional guar, gel breaking experiment and assessment of repeated crosslinking performance, the fast hydrating guar performance and reutilization feasibility was studied. The experimental results show that, the fast hydrating guar dissolved fast, with a good dispersion property and completely gel breaking performance, which can be as a thickening agent consisting of fracturing fluid system with shear resistant performance, a certain reutilization performance, economy and environmental protection, has a wide application prospect.